Analisis Bibliometrik Publikasi Manajemen Pendidikan Tinggi - Adiatma, Tini; M, Nursafitra (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
This study aims to examine the development of publications related to higher education management. This research aims to discover the development trend of the number of studies and the mapping of research study themes. This study uses bibliometric analysis of data taken with the keyword